El rol del sector hidrocarburos en la transición energética (2021)
This paper presents to reader information related to the Plan Energetico Nacional 2050 led by the national government, addressing the following topics: Analyzes schemes adopted in leading countries in the world and in leading companies in the oil industry, in energy transition. It presents the relevant points of Plan Energetico Nacional 2050 regarding the country's energy transition. It exposes the participation of the hydrocarbon sector in the national economy, considering the projections of the PEN 2050 Define the technical-environmental participation of the hydrocarbon sector in the development of the national energy transition aligned with the PEN 2050.